ANALISIS PELAKSANAAN PROMOSI PADA INDUSTRI KECIL KERIPIK MAI SATUN-DUMAI - Edi Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
ing able to survive in the ever increasing level of competition, one aspect that needs to be considered in a company is the marketing aspect, namely how to get goods or services to be acceptable and to provide satisfaction to consumers. As part of the promotion marketing mix also has a significant influence on the company's efforts to achieve maximum sales targets. This research was conducted on the small industry of Mai Satun chips in Dumai City. The purpose of this research will be to examine the promotion of the small Satun-Dumai chips industry. In this research use quantitative descriptive method. Respondents from this research are customers or consumers of the small Satun Industry chunks that happen to come at the time of the questionnaire spread. This is because this research uses accidental sampling technique. And as a source of information is the owner of the small Satun-Dumai chips industry. Data collection techniques through interviews, and questionnaires. From the result of questionnaire spread can be concluded that in the implementation of promotion of small industry of Mai Satun chips included in category of poor.Keywords: Promotion